The toxicology and biochemistry of insecticides - Yu, Simon J. (Boca Raton, FL : CRC Press, 2008)
Despite their potentially adverse effects on nontarget species and the environment, insecticides remain a necessity in crop protection as well as in the reduction of insect-borne diseases. The Toxicology and Biochemistry of Insecticides provides essential insecticide knowledge required for the effective management of insect pests. Continuing as the sole book in more than two decades to address this multifaceted field, the Second Edition of this highly praised review on insecticide toxicology has been greatly expanded and updated to present the most current information on: Systemic classification of insecticides (Chapter 4) How insecticides function at the molecular level and newly discovered modes of action (Chapter 7) Insecticide resistance, molecular mechanisms, fitness costs, reversion, and management of resistance (Chapter 10) Various bioassay methods including the interpretation of probit analysis (Chapter 5) Molecular mechanisms of insecticide selectivity (Chapter 9) Major biochemical mechanisms involved in the transformation of insecticides (Chapter 8) Fate of insecticides in the environment and the sublethal effects of insecticides on wildlife (Chapter 11) Newly developed insecticides, including the addition of more microbial insecticides in keeping with current integrated pest management (IPM) approaches (Chapter 4) Incorporating extensive reference lists for further reading, The Toxicology and Biochemistry of Insecticides, Second Edition is an ideal textbook for students of entomology, plant medicine, insecticide toxicology, and related agricultural disciplines. It is also a valuable resource for those involved in insecticide research, environmental toxicology, and crop protection. -- Provided by publisher.
Need for pesticides and their pattern of use -- Formulation of pesticides -- Pesticide laws and regulations -- Classification of insecticides -- Evaluation of toxicity -- Uptake of insecticides -- Mode of action of insecticides -- Principles of pesticide metabolism -- Species differences and other phenomena associated with the metabolism of xenobiotics -- Insecticide resistance -- Pesticides in the environment.
A CRC title.
Includes bibliographical references and index.
Keywords: Insecticides